Perceived violations of reward delivery obligations in reward-based crowdfunding: An integrated theoretical framework - Anthony Macari; Grace Chun Guo (New England Journal of Entrepreneurship (NEJE), 2021)
Purpose This conceptual paper focuses on a common observation in the implementation stage of reward-based crowdfunding (RBC) - entrepreneurs' failures and delays in delivery of rewards to investors, which, in turn, may be perceived as violations of reward delivery obligations. Design/methodology/approach Drawing on entrepreneurial personality theory and psychological contract theory, this paper develops propositions and identifies factors related to both entrepreneurs (overconfidence and narcissism) and factors related to investors (types of motivators and psychological contracts) that may explain the perceived violations of reward delivery obligations. Implications for theory and practice are also discussed. Findings The theoretical analysis, by wielding two independently developed literatures, has demonstrated that it is important to investigate factors that are related to both investors and entrepreneurs in understanding issues and challenges at different stages of the RBC model. The authors believe that the current analysis provides an integrated understanding and a solid foundation for researchers to further examine these issues by empirically testing these propositions. Originality/value The authors examined two previously understudied psychological factors in the context of RBC - entrepreneurial traits, mainly overconfidence and narcissism, and the type of psychological contracts formed between investors and entrepreneurs, both of which, according to McKenny et al. (2017), need greater attention from researchers studying crowdfunding.
Keywords: 650; Crowdfunding platforms; Entrepreneurial personality; Failure and delay in reward delivery; Investor motivators; Legal issues; Narcissism; Overconfidence; Perceived violation of reward delivery obligation; Psychological contracts; Reward-based crowdfunding